Periodontal disease and quality of life in patients with circulatory diseases - Luana TAQUES; Lourdes Zeballos LÓPEZ; Lauro TAQUES NETO; Guilherme ARCARO; Erildo Vicente MULLER; Fabio André dos SANTOS; Marcia Thaís POCHAPSKI (Universidade Estadual Paulista, 2023)
Abstract Introduction Circulatory system diseases are one of the leading causes of death. Periodontal health is a component of oral and general health that contributes to quality of life. Objective To analyze periodontal conditions and quality of life in patients with circulatory diseases. Material and method Cross-sectional study, with patients with circulatory diseases (n=125). The clinical periodontal examination was performed considering: biofilm, bleeding on probing, suppuration, probing depth, gingival recession, and clinical attachment level. Quality of life was assessed with the Medical Outcomes Study 36 - Item Short-Form Health Survey (SF-36) and Oral Health Impact Profile - short form (OHIP-14). Data were analyzed with parametric and nonparametric tests (α=5%). Result Elderly and men had a greater severity of periodontal disease. The Elderly had lower values in the domains of "Functional capacity" and "Physical aspects" (SF-36). The domain "Pain" had lower values in subjects with health/gingivitis. OHIP-14 did not show differences in the comparisons. There was no correlation between quality of life and the severity of periodontal disease. Conclusion Among patients with circulatory diseases, the elderly and men had greater severity of periodontal disease. The elderly had a poorer quality of life (functional capacity and physical aspects). There was no correlation between the severity of periodontal disease and quality of life.